(untitled) (Scientific journal of the Fergana State University, 2023)
Calliptamus italicus.L (local raw material) was chosen as a source for chitosan extraction. We studied the physicochemical properties, such as: the degree of deacetylation (DDA), molecular weight, elemental analysis (ICP-MS) and (CHNS), IR and Roman spectra of the isolated chitosan.